The Zen of groups a handbook for people meeting with a purpose - Hunter, Dale 1943- (Gower Publishing, 1992)
This work is designed to make the reader a more effective member of any group, and to show how the effectiveness of the group itself can be greatly increased. Practical advice and numerous exercises are provided. Thinking points and a toolkit of 95 techniques are provided.